STUDENTS’ MASTERY OF SYSTEMIC FUNCTIONAL GRAMMAR AND ITS CLASSROOM IMPLEMENTATION: A NATURALISTIC STUDY AT ENGLISH DEPARTMENT OF TIDAR UNIVERSITY - Dwi Winarsih (Jurnal Penelitian Humaniora, 2014)
English language teaching in Indonesia which is text-oriented concerns with text type or genre. The teaching is based on the concept that language is a system of choice by which writers can communicate certain functions allowing them to express their experiences, to  interact with others, and to create coherent message. Consequently, systemic functional grammar which views language as a strategic, meaning-making resource is implemented. However, the facts show students of English Department have limited knowledge on it. Their average score of the examination is unsatisfactory, below 70. The objectives of the research are to describe (1) the students’ mastery on interpersonal metafunction, experiential metafunction, and textual metafunction; and (2) to describe the classroom implementation systemic functional grammar course.This is a naturalistic study conducted at English Department. The subjects of this research are one lecturer and 30 students taking structure 3 course. Data are collected from teaching-learn- ing activities and relevant documents. The result indicates that students’ mastery of systemic functional grammar is low. They get confused when they come across with complex clauses in spoken text.